Chimeric antigen receptor‐modified human regulatory T cells that constitutively express IL‐10 maintain their phenotype and are potently suppressive. Issue 10 (8th August 2021) - Mohseni, Yasmin R.; Saleem, Adeel; Tung, Sim L.; Dudreuilh, Caroline; Lang, Cameron; Peng, Qi; Volpe, Alessia; Adigbli, George; Cross, Amy; Hester, Joanna; Farzaneh, Farzin; Scotta, Cristiano; et al.
Abstract: Clinical trials of Treg therapy in transplantation are currently entering phases IIa and IIb, with the majority of these employing polyclonal Treg populations that harbor a broad specificity. Enhancing Treg specificity is possible with the use of chimeric antigen receptors (CARs), which can be customized to respond to a specific human leukocyte antigen (HLA). In this study, we build on our previous work in the development of HLA‐A2 CAR‐Tregs by further equipping cells with the constitutive expression of interleukin 10 (IL‐10) and an imaging reporter as additional payloads. Cells were engineered to express combinations of these domains and assessed for phenotype and function. Cells expressing the full construct maintained a stable phenotype after transduction, were specifically activated by HLA‐A2, and suppressed alloresponses potently. The addition of IL‐10 provided an additional advantage to suppressive capacity. This study therefore provides an important proof‐of‐principle for this cell engineering approach for next‐generation Treg therapy in transplantation. Abstract : Chimeric antigen receptor (CAR) constructs can be modified to incorporate elements for enhanced activity. Here, human Tregs were modified to express an anti‐HLA‐A2 CAR as well as IL‐10 and an imaging reporter. These cells maintained a stable Treg phenotype after lentiviral transduction, were specifically activated by cells expressing HLA‐A2, and had enhanced in vitro suppressive potency compared with CAR Tregs without constitutive IL‐10 expression.